Effect of Health Education on Cervical Cancer’s Early Detection on Knowledge of Women of Fertile Age - Tamunu, Esther Novilian; Lombogia, Moudy; Tahir, windy Mochtar (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background: Cervical cancer cervical or cancer is a type of cancer that affects the surface layer of the cervix or cervix. This type of cancer is one of the types of cancer that ranks first and is the most experienced by women around the world (Savitri, 2015). Purpose: This study aims to determine the effect of health education on knowledge of women of childbearing age (WUS) about early detection of cancer cervical. Methods: This research use research literature review using the results of previous studies, textbooks or research journals. To obtain data that is in accordance with the topic of discussion, the researcher conducted a search for national and international-based journals on three databases, namely Scient direct, PUBMED, and Google Schoolar using the keywords health education,cancer early detection cervical, and knowledge. The keywords used are listed in each journal title obtained with the provisions of the journal being sought, namely from 2016-2020 then the journals obtained were selected and the researcher determined 8 journals that were in accordance with the topic of discussion of literature review. Results: Based on eight literature reviews, the results of the study stated that health education had an effect on one's knowledge. This indicated that a person's knowledge could change in an increased sense after being given health education about early detection ofcancer cervical. Conclusion: There is an effect of health education on knowledge of women of childbearing age (WUS) about early detection of cancer cervical Keyword : Health education, Detection of cervical cancer, Knowledge